Rheology and Stability Mechanism of Water-in-crude Oil Emulsions Stabilized by Span 83 - Akbari, Sweeta; Nour, A. H.; Saidatul Shima, Jamari; Fayaz, Fahim (Asian Research Publishing Network (ARPN), 2016)
Water-in-crude oil (W/O) emulsions are found in many industries such as cosmetic, pharmaceutical, and petroleum. The study was aimed to investigate the rheological properties and the stability mechanism of W/O emulsions at different water to oil ratios of (20-80 vol.%) and (40-60 vol.%). The emulsions were stabilized by a non-ionic surfactant (Span 83) at concentrations of 1.5-2.5 vol.%. The heavy and light crude oils were mixed at 50-50 vol.% and characterized in terms of physical and chemical properties. From the results, it was found that the emulsion with higher water volume fraction obtained more viscosity with larger droplet sizes which present low stability. As well as, the higher viscosity was obtained in emulsion with higher emulsifier concentration (2.5 vol.%). However, 20-80 % W/O emulsion and emulsions stabilized with 2.5 % Span 83 produced more stable emulsions as observed through the optical microscopy images. In order to determine the dynamic viscosity, different temperatures from (30 to 90 ºC) and spindle rotational speeds from (50 to 250 rpm) were used. Furthermore, all types of prepared emulsions were visually stable over a period of more than one week, where no water separation was observed during this period, besides; they exhibited a non- Newtonian shear thinning fluid behavior.